Pengembangan Soal Matematika Model Pisa Menggunakan Konteks Palembangan - Rizki Putri Mayari; Yuli Fitrianti; Muslimahayati Muslimahayati (JURNAL MathEdu (Mathematic Education Journal), 2022)
PISA model mathematical problem development using the Palembang context is an alternative to improve student mathematical abilities or student’s mathematical literacy. This type of research is a development research consisting of a preminary stage ( preparation and design ) and a prototyping stage using a formative evaluation design flow including the self-evaluation, expert review, one-to-one, small group and field test stages. This study aims to explain the validity and practicality of the PISA model mathematical problems using the Palembang context. And has a potential effect on student learning outcomes. As for the subjects in this study were the SMP Negeri 22 Palembang school in class VIII.1, totaling 29 people. This research resulted in: 1). The PISA model mathematical problem using the Palembang context which is classified as valid. 2). The PISA model mathematics problem using the Palembang context which is classified as practical. 3). How do students' mathematical literacy skills after using the PISA model math problems using the Palembang context